Cathodic Determination of Naproxene and Paracetamol in Biological Liquids and Wastewater: A Theoretical Insight - Tkach, V. V.; Kushnir, M. V.; de Oliveira, S. C.; Ivanushko, Y. G.; Kryvetskyi, V. V.; Kryvetska, I. I.; Kryvetskyi, I. V.; Yagodynets', P. I.; da Silva, Adriano O.; Derevianko, N. P.; Zavhorodnii, M. P.; Serhata, N. S.; et al. (My University, 2025)
The possibility of the cathodical determination of naproxene and paracetamol has been theoretically analyzed. The process may be realized in neutral and mildly acidic media, in which the conducting polymer is recommended as an electrode modifier. From the steady-state stability point of view, the electroanalytical process is stable and efficient. Nevertheless, the topological zone of the linear dependence between the analytes concentration and electrochemical parameter becomes dependent on the conducting polymer nature being different for ionic and non-ionic monomers.
Keywords: naproxene; paracetamo; electrochemical sensors; conducting polymers; stable steady-state